2023
DOI: 10.56238/isevjhv2n2-002
|View full text |Cite
|
Sign up to set email alerts
|

Influência das fases do ciclo menstrual na capacidade de força no treinamento resistido

Abstract: It is known that resistance training for women brings several benefits such as improved health, physical and emotional well-being, and improved strength capacity, and can also help in the menstrual cycle. Most women believe that menstrual symptoms such as weight gain, cramps, bloating, and discouragement are factors for the loss of muscle performance; however, regular and periodized training according to the biological individuality can minimize these symptoms. The objective of the study was to carry out a bib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Recent reviews have shown very heterogeneous results [ 27 , 56 , 57 , 58 , 59 ] due to the multiple influencing factors within the cycle phases, although to the authors’ knowledge, no systematic review has explicitly examined the effects on maximal strength. This provides the rationale for this systematic review and meta-analysis, namely, to both provide initial insights into differences in maximal strength and develop further practical implications.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reviews have shown very heterogeneous results [ 27 , 56 , 57 , 58 , 59 ] due to the multiple influencing factors within the cycle phases, although to the authors’ knowledge, no systematic review has explicitly examined the effects on maximal strength. This provides the rationale for this systematic review and meta-analysis, namely, to both provide initial insights into differences in maximal strength and develop further practical implications.…”
Section: Introductionmentioning
confidence: 99%